Estudo prospectivo controlado, comparando fisioterapia e fisioterapia mais descompressão em pacientes com estenose do canal lombar sintomáticos - Rodrigues, Luiz Claudio Lacerda [UNIFESP] (2017)
The lumbar spinal canal stenosis was first described by Antoine Portal in 1803. However, the first association between changes in the diameter of the spinal canal and its relation to the clinical condition and the neurogenic claudication was made by Verbiest. In this study, we evaluated 63 patients with lumbar canal stenosis, of both genders and age between 50 and 75 years. Of all, 31 were submitted to surgery and physiotherapy and 32 only to physiotherapy. All of them passed through five analyzes, made by a blinded evaluator, and performed a twice weekly exercise program for three months. As an evaluation tool, we used the six-minute walk test; the Roland-Morris, SF-36 and Oswestry questionnaires; and a Likert scale. The mean age of the operated patients was 60.7 years and, among the non-operated, 60.2 years. In the gender division, 8 men and 23 women underwent surgery and 8 men and 24 women belonged to the control group. Systemic arterial hypertension was the chronic-degenerative disease with a higher incidence in the study patients. We observed that, except for Oswestry questionnaire, which evaluated functional capacity, and for the Likert scale, which presented statistically significant results, we did not find significant differences between the groups. The gait capacity did not change after the surgery. Their quality of life, when analyzed by SF-36, did not confer a statistically significant difference, but after one year of follow-up, the operated patients were more satisfied than the others. Isolated physiotherapy did not show improvement in the patients’ condition. We concluded that the surgery with physiotherapy or isolated physiotherapy does not modify, in a statistically significant way, the patient’s quality of life, nor do any of the therapies evaluated effectively improve the distance that they manage to wander. Operated patients have a statistically significant improvement perception in relation to the control group and also presented an improvement in overall functional capacity after surgery. In our study, the surgery proved to be safe, having observed no complication or need for reoperation in the intervention group.